Deblurring Photos with Lucy-Richardson and Wiener Filter Algorithm in RGBA Color - Michiavelly Rustam; Agung Brotokuncoro; Wiranto Herry Utomo; Hasanul Fahmi (Jurnal Media Infotama, 2025)
Photographers and social media influencers encounter challenges with hand tremors during photo capture, leading to unintended blurriness in their posts, reducing visual impact and audience engagement. To mitigate this problem, the authors aim to effectively reduce the blurring caused by instability in handling, producing sharper and noise-free photos. The methodology involves implementing the Lucy-Richardson and Wiener Filter algorithms into a Python-based web application optimized for RGBA photo processing. Data requirements include sample photos affected by hand tremors to validate the efficacy of the solution. The outcome successfully eliminates blur in captured photos affected by hand tremors in RGBA color format.